2000
DOI: 10.1002/(sici)1099-1409(200003)4:2<158::aid-jpp156>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer in the redox reaction of cobalt tetraphenylporphyrin incorporated in a Nafion film

Abstract: Potential step chronoamperospectrometry (PSCAS) was carried out to analyze electron transfer in the redox reaction processes of 5,10,15,20-tetraphenylporphyrinatocobalt(II) ( Co II TPP (-2)) incorporated in a Nafion film. The reactions of Co II TPP (-2) to [ Co III TPP (-2)]+ and of [ Co III TPP (-2)]+ to Co II TPP (-2) took place through a diffusion mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Polymer-coated electrodes have been extensively studied because of their potential applications in electrocatalysis [13,14], electrosynthesis and molecular electronics and as substrates for immobilization of enzymes [15]. The underlying motivation for electrode surface modifications stems from the desire for improved electrocatalysis and freedom from surface fouling effects [16].…”
Section: Introductionsupporting
confidence: 92%
“…Polymer-coated electrodes have been extensively studied because of their potential applications in electrocatalysis [13,14], electrosynthesis and molecular electronics and as substrates for immobilization of enzymes [15]. The underlying motivation for electrode surface modifications stems from the desire for improved electrocatalysis and freedom from surface fouling effects [16].…”
Section: Introductionsupporting
confidence: 92%
“…Among these, Nf has been used as a functional material due to notable features that include its superior chemical and photothermal stabilities, filming properties, and, more importantly, its hydrophilic -SO 3 – ionic-cluster regions, hydrophobic fluorocarbon regions, and the interfacial regions that are formed between them that makes it more suitable than other polymers for sensing applications [ 30 ]. It has been reported that metalloporphyrins occupy the hydrophobic and interfacial regions of the Nf film due to their hydrophobic nature [ 31 ]. Moreover, the polyvalent ampholytic nature of the tetrakis(4-nitrophenyl)porphyrin (TNPP) inner core provides sensitivity toward bases and acids [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption energy of NO and NH 3 in the presence of an electric field was higher than that in the absence of electric field, indicating that the amount of adsorption of NO and NH 3 were enhanced by the presence of tourmaline; at the same time, the performance of the catalyst was promoted. Electron transfer reaction is the basic step of redox reaction [21], it is also the principle behind how the catalyst works. The spontaneous electric field of tourmaline can speed up proton and electron transfer, increase the degree of electron activation, raise the collision probability between reaction gas and catalyst and then promote the adsorption of NO and NH 3 , ultimately speeding up the chemical reaction rate.…”
Section: Dft Studymentioning
confidence: 99%